Ischaemic infarct of the brain stem combined with bisymptomatic Klippel-Trénaunay-Weber syndrome and cutis laxa. Issue 6 (June 1976) - Alberti, E
Abstract : The combination of Klippel-Trénaunay-Weber syndrome (KTWS) with intracranial vascular malformations is documented by angiography in a 25 year old man with the classical features of KTWS: systematized naevi, hypertrophy of the right side, and varicosis. In addition, the syndrome was associated with "cuts laxa", a coincidence of somar rarity. The patient suffered from an ischaemic infarct of the brain stem with several neurological deficits.